Pengaruh Kualitas Produk, Citra Merek, Dan Persepsi Harga Terhadap Kepuasan Konsumen Smartphone Iphone Melalui Keputusan Pembelian Sebagai Variabel Intervening - Naufal Mubarak; Sri Murtiasih (Forum Kerjasama Pendidikan Tinggi, 2022)
This research is motivated by competition for Smartphone products which are one of the drivers of digital-based community activities. With so many new smartphones that have sprung up, it forms a competition between smartphone manufacturers to become the market leader and achieve a company's desire and profit. The purpose of this study was to determine the effect of product quality, brand image, and price on consumer satisfaction with purchasing decisions as an intervening variable. This research includes the type of associative research and quantitative approach. The data used in this study is primary data obtained by distributing questionnaires to consumers who have used or are currently using an Iphone smartphone. The sampling technique used non-probability sampling technique with purposive sampling method obtained a total sample of 100 people. The test stages carried out are validity test, reliability test, normality, multicollinearity, heteroscedasticity, coefficient of determination test, f test, t test and the data analysis technique used to answer the hypothesis is path analysis. The testing tool used is SPSS 25. The results of this study indicate that there is a positive and significant effect on the variables of Product Quality, Price, and Purchase Decision on Consumer Satisfaction, while the Brand Image variable has no significant effect on Consumer Satisfaction. Then there is a positive and significant influence on the Product Quality and Price variables on Purchase Decisions, while Brand Image does not have a significant effect on Purchase Decisions. And there is a positive and significant influence on the variables of Product Quality, Brand Image, and Price on Consumer Satisfaction through Purchase Decisions on Iphone Smartphones.